Impact of Malaria on Hematological Profiles, Iron Indices, and G6PD Activity in Pregnant Women - Fidelis Ohiremen Oyakhire; Patricia Ejenawome Dele-Ochie; Juliana Edusola Olaniyan; Valentine Ikalumhe; Babatunde Ishola Gabriel Adejumo; Samson Efenarhua; Osamwonyi Ernest Igbinovia; Emmanuel Onosetale Afeikhena; Adebukola Adisa Ekoh-Jolly (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2026)
The global prevalence and impact of malaria on pregnancy highlight a significant public health challenge that demands enhanced preventive measures and targeted interventions. The study aimed to assess the hematological, iron, and G6PD status among pregnant women infected with Plasmodium falciparum. We performed a comparative cross-sectional study among two hundred (200) pregnant women infected with Plasmodium falciparum, who attended Edo Specialist Hospital, Benin City, to assess the hematological, iron, and G6PD status compared with fifty (50) Plasmodium falciparum-free pregnant women as controls. Hematological parameters, iron, TIBC (total iron binding capacity), and G6PD activity were assessed using a hematology auto analyzer and spectrophotometric methods, respectively. Data obtained were analyzed using SPSS (IBM v26). Independent t-test and one-way analysis of variance (ANOVA) were used for continuous variables, and chi-square was used for categorical variables. Pregnant women infected with Plasmodium falciparum had 8.70%, 9.42%, 14.44%, 8.1%, 20.17%, 16.72%, 11.31%, and 27.8% reduction in red blood cell, hemoglobin, iron, packed cell volume, G6PD, total iron binding capacity, monocyte, and lymphocyte levels, respectively, compared to Plasmodium falciparum-free pregnant women as controls (p<0.05). In addition, the levels of white blood cell, platelets, and neutrophils witness 15.58%, 10.85%, and 24.02% increase in pregnant women infected with Plasmodium falciparum compared with plasmodium falciparum free pregnant women as controls (p<0.05). No significant differences were observed in serum iron and G6PD levels across gestational ages (p>0.05). The findings underscore the need of regular monitoring of hematological and biochemical parameters in pregnant women infected with Plasmodium falciparum in order to enhance policy on malaria prevention and screening in endemic regions.